Application and Verification of Techniques for Visually Assessing Pasture Conditions in Mountainous Terrain: A Test of Three Field Assessment Methods in the Kyrgyz Republic - Peter Kirch; Thomas Heinicke; Graham Shepherd; Jutta Zeitz (Mountain Research and Development, 2016)
The objective of this study was to determine a reliable and effective way to visually assess pastures under the site conditions that prevail in the Kyrgyz Republic, in particular the mountainous terrain. Such a method should make a visual evaluation of pasture conditions in the field possible and help build awareness among land users of soil and pasture degradation and the need for sustainable use of pasture areas. To this end, the Visual Soil Assessment (VSA) method was applied and verified in a research area in the Naryn district in the Kyrgyz Republic. This process included the application of 2 additional visual site assessment methods—the Muencheberg Soil Quality Rating and the method described in the Monitoring Manual for Summer Pastures in the Greater Caucasus in Azerbaijan by Etzold and Neudert in 2010, referred to subsequently as the MMSP method. A comparison of the VSA results to standard field measurements and laboratory-based analysis was also performed. The VSA method was found to be only moderately applicable under the site conditions, with low correlation between the indicator ratings and the results of the standard measurements. The MMSP method showed substantially better applicability. The results of the study suggest that further research is needed to refine the MMSP method to develop an effective visual assessment method that can be used to support sustainable use and protection of pasture areas in mountain regions.